HUBUNGAN ANTARA KOMPONEN RUMAH DENGAN KEJADIAN PENYAKIT ISPA DI WlLAYAH KERJA PUSKESMAS WONOKUSUMO KOTA SURABAYA - Maramis Puji Darma; Khambali .; Setiawan . (GEMA LINGKUNGAN KESEHATAN, 2013)
Home environment give influence on upper way respiration disease (ISPA) asenvironment based disease indicated by improving ISPA incidence because of unhealthy homeand residential. Wonokusumo public health center during last five years ISPAalways positionedfirst ranking in Top 10 diseases with average more than 10.000 cases. This research done torecognize correlation between home component and ISPA incidence in Wonokusumo publichealth center Surabaya region in 2013.Analytic research method done with case control. This research compare between casegroup and control group. Sample taken as many 94 houses for case group respective andcontrol group with population 10.013 patients. Sampling technique using simple randomsampling with data analysis method using chi square test.The assessment result explain that house component assessment aspects which meetrequirement house component assessmentaspects are ceilings, wall, floor, living room window,and lighting. While unmeet requirement are bedroom aspects, ventilation, and kitchen fumecavity. Most of case group have home component is unmet requirements with percentage79.8% and most of control group as many 74.5%. The result of the research indicating thatthere are no correlation between house components and ISPAdisease incidence.Suggested health workers give information, citizen hoped to keep house cleanliness andheld contest about health home in order to citizen more motivated again for more improvinghouse that meeting healthy requirements.Keywords: House component, ISPAincidence, health house.